Multidisciplinary Approaches to Diabetes Control: Insights from Nursing, Laboratory Medicine, Clinical Pharmacy, and Health Informatics - Atheer Yahya Ahmed Albaraq; Noor Maitham Nasser Alahmed; Nouf Turki Hamad Alshomrani; Majedah Abdullah Ali Alameer; Naif Dawas Talaa Alharbi; Fahad Saadah Sulaiman Alsulobi; Abdurhman Mohammed Hazzazi; Ali Mohammed Hazzazi; Hazem Mohammed Alharbi; Ameen Hamoud Ahmed Mashyakhi; Fahad Abdullah Alharbi; Hussein Yahya Abdullah Al-Harith (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Diabetes mellitus is a chronic metabolic disease that is defined by chronically raised blood glucose level and is among the leading health threats in the world. Diabetes is a complicated task to manage since it has so many facets. These include roles of nursing, laboratory medicine, clinical pharmacy, health informatics that all contributes to the improvement of patient outcomes and provide perspectives of each discipline on diabetes based on the model. Aim of work: To examine the roles of nursing, laboratory medicine, clinical pharmacy, and health informatics in diabetes control, highlighting the benefits of an integrated approach for improved patient outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Multidisciplinary, Approach, Diabetes Control, Nursing, Laboratory Medicine, Clinical Pharmacy, and Health Informatics. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:There is awareness of Multidisciplinary team diabetes where the care of any diabetic patient involves several health disciplines to ensure holistic care. For glycemic control, roles and contributions of several fields are nurses, laboratory professionals, pharmacists, and health informatics specialist. This combination of care shows the medical, psychological and social side of diabetes patients, which emphasizes on the urgent need for a more holistic approach to managing diabetes in general and a need to adopt more integrated models of care in particular in the face of a growing global diabetes threat.